The impacts of the COVID-19 pandemic on birth satisfaction in a prospective cohort of 2, 341 U.S. women. Issue 5 (September 2022) - Preis, Heidi; Mahaffey, Brittain; Heiselman, Cassandra; Lobel, Marci
Abstract: Problem: Birth satisfaction is an important health outcome that is related to postpartum mood, infant caretaking, and future pregnancy intention. Background: The COVID-19 pandemic profoundly affected antenatal care and intrapartum practices that may reduce birth satisfaction. Aim: To investigate the extent to which pandemic-related factors predicted lower birth satisfaction. Methods: 2341 women who were recruited prenatally in April–May 2020 and reported a live birth between April–October 2020 were included in the current analysis. Hierarchical linear regression to predict birth satisfaction from well-established predictors of birth satisfaction (step 1) and from pandemic-related factors (step 2) was conducted. Additionally, the indirect associations of pandemic-related stress with birth satisfaction were investigated. Findings: The first step of the regression explained 35% of variance in birth satisfaction. In the second step, pandemic-related factors explained an additional 3% of variance in birth satisfaction. Maternal stress about feeling unprepared for birth due to the pandemic and restrictions on companions during birth independently predicted lower birth satisfaction beyond the non-pandemic variables. Pandemic-related unpreparedness stress was associated with more medicalized birth and greater incongruence with birth preference, thus also indirectly influencing birth satisfaction through a mediation process. Discussion: Well-established contributors to birth satisfaction remained potent during the pandemic. In addition, maternal stress and restriction on accompaniment to birth were associated with a small but significant reduction in birth satisfaction. Conclusion: Study findings suggest that helping women set flexible and reasonable expectations for birth and allowing at least one intrapartum support person can improve birth satisfaction.